This comment was posted to reddit on May 06, 2022 at 1:12 pm and was deleted within 5 hour(s) and 37 minutes.

Ok so basically an²+bn-4 was the expression given. We know from the question that when n =1, the first term is -3 and when n=2, the second term is 2

So we hv to do a(1)²+b(1)-4 = -3 which gives us a+b=1

We then had to do the same for when n=2 so it would be a(2)²+b(2)-4 = 2 giving us 4a+2b = 6 which is 2a+b=3 when simplified

Now we have both our simultaneous equations so we just solve for either a or b (im gonna be solving for a for this example)

a+b=1 (multiply by -1) 2a+b=3

-a-b=-1 2a+b=3 a=2

then we just substitute the value of a into the equation for either the first term or second term (im gonna be choosing first)

2(1)²+b(1)-4=-3 2+b-4 = -3 b = -1